Improving Students’ English Grammar Through Incorporating Games - Fauzi, Khalif Rahma Riesty; Munawaroh, Hidayatul; Sulistyaningsih (ETERNAL (English Teaching Journal), 2024)
This classroom action research aimed to enhance English grammar learning at a junior high school level by incorporating game-based activities, focusing on the simple present tense. The primary objective was to address identified challenges, such as low student enthusiasm and understanding of grammatical concepts. The study used classroom action research, unfolded in three cycles, each refining the game-based approach based on insights from the previous cycle. The methodology involved pre-tests, game-based lessons, observations, and reflective assessments. Results demonstrated sustained improvements, with increased scores and active participation. Key findings indicated enhanced active participation, motivation, concept understanding, collaboration, spontaneous English use, and a deeper understanding of the game-based method's shortcomings. The time required for understanding they were varied, reflecting the effectiveness of scaffolding in the learning environment. Implications of the research suggest the continued integration of game-based approaches, recognizing the diverse learning needs of students. Teachers should tailor scaffolding strategies to individual ZPDs, fostering collaboration and addressing language apprehension. The study contributes to the broader discourse on effective language teaching methodologies, emphasizing the dynamic interplay of theory and practice in the language learning classroom.